Sinergitas Pemerintah Desa Tangkas Kecamatan Klungkung dengan TPS3R (Tempat Pengelolaan Sampah Reduse, Reuse, Recycle) Darma Winangun untuk Meningkatkan Partisipasi Masyarakat dalam Mewujudkan Kesehatan Lingkungan - Krisna Bayu, I Gede Agus; Winaya, I Ketut; Dwi Wismayanti, Kadek Wiwin (CITIZEN CHARTER, 2019)
ABSTRACT Health is a desire for all people in each region both in the city and in the village. Indonesia itself has Law No. 18 of 2008 concerning Waste Management, this is proof of the government's seriousness in terms of combating waste, which is increasing in number each year and also various characteristics of Tangkas Village, Klungkung Subdistrict, Klungkung Regency is one of the villages in Bali that has its own way of dealing with waste issues starting from the village level. The results of this research show the collaboration between Tangkas Village Government and TPS3R Darma Winangun (Reduse Waste Management Site, Reuse, Recycle) has continued to strive to always invite Tangkas Village people to care more about waste problems and their impact on the environment, the role of the Village Government Tangkas and TPS3R (Reduse Waste Management Site, Reuse, Recycle) Darma Winangun should have a short-term goal by determining the achievement of the number of customers of Darma Winangun's TPS3R (Reduse Waste Management, Reuse, Recycle). Keywords: Synergy, Community Participation, Environmental Health.